IMPLEMENTASI TEORI HUMANISME DALAM MEMBENTUK KARAKTER TANGGUNG JAWAB SISWA PADA PEMBELAJARAN PAI - Oktaviani, Dewi Ratnasari; Rohmani, Abd. Hadi (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2025)
In the era of globalization marked by a moral crisis, education plays a crucial role in shaping students' character. sThis study aims to address three main research questions: how humanistic theory is implemented in fostering students' sense of responsibility in PAI learning at UPT SD Negeri 355 Gresik, what factors influence its success, and what challenges teachers face during the process. Employing a qualitative approach, data were collected through observation, interviews, and documentation. The findings reveal that humanistic theory is applied through student-centered learning involving methods such as discussion, reflection, simulation, and project-based activities. Supporting factors include teacher competence, student motivation, active participation, a supportive school environment, and parental involvement. On the other hand, key challenges include limited instructional time, insufficient learning resources, and the negative influence of social media. Despite these obstacles, teachers manage to instill responsibility through empathetic and contextual approaches. The study recommends strengthening collaboration between schools and families, as well as enhancing the availability of resources that support humanistic learning.